Diseminasi dan Pendampingan Pembangunan Peternakan Terintegrasi untuk Peningkatan Kesejahteraan Peternak dalam Upaya Pencegahan Stunting di Desa Cijulang, Kabupaten Pangandaran - Ismiraj, Muhammad Rifqi; Mutaqin, Bambang Kholiq; Yuniarti, Endah; Wulansari, Asri (Farmers : Journal of Community Services, 2026)
Stunting remains a chronic public health problem in Indonesia. Recent data indicate that 27.6 % of Indonesian children under five experience stunting, far above the World Health Organization (WHO) target, reflecting unequal access to health services, clean water, sanitation and feeding practices. This community‑service program aims to improve farmer welfare and reduce stunting in Cijulang village by integrating intensive sheep farming with family nutrition gardens and organic waste management. A community‑based approach involved designing an integrated farming system, training farmers and health cadres, establishing communal sheep pens and nutrition gardens, and monitoring child growth. Baseline surveys showed that 60 % of farming families consumed animal protein only twice per week. After training and implementation, communal pens housing 30 sheep were constructed and 100 m² of gardens planted. Farmers learned silage and compost making, with post‑training knowledge rising by 40 %. Households increased animal‑protein consumption to at least four times per week, and child height‑for‑age z‑scores improved by 0.3 within six months. Integrating sheep farming, nutrition gardens and waste recycling offers a practical model for enhancing household food security, income and child nutrition.